A Computer-Assisted Writing Tool for an Extended Variety of Leichte Sprache (Easy-to-Read German) - Harbusch, Karin; Steinmetz, Ina (Frontiers in Communication, 2022)
Leichte Sprache (LS; Easy-to-Read German) is a simplified variety of German characterized by simplified syntactic constructions and a small vocabulary (cf. Easy-to-read English). It provides barrier-free information for people with cognitive impairments or learning difficulties and/or a low level of literacy in the German language. Recently, the difficulty level of syntactic constructions — not only within, but also beyond the scope of LS — was systematically evaluated with LS readers as part of the LeiSA project (Bock, 2019). Based on quantities retrieved from a collection of 245 LS documents (more than 300,000 words) from various sources spanning the years 2018 – 2021, we explore how often these constructions occur compared to “ordinary” spoken and written German (i.e., texts that were not produced with the explicit goal of facilitating comprehensibility). Evaluating ease of perception, frequencies in the three treebanks, and difficulty to circumvent a construction, we define the range of Extended Leichte Sprache (ELS) — altogether, a small, but native expansion. In order to enable ELS-text production for the above-mentioned target group, we developed a computational linguistic system, dubbed ExtendedEasyTalk. It supports LS readers in formulating grammatically correct and semantically coherent texts. Here, we outline the principal components: (1) A natural-language paraphrase generator that supports fast and correct ELS text production while taking readership-design aspects into account; and (2) explicit Rhetorical Relation Theory (RST)-inspired coherence specifications to express the communicative function of the sentences. The writing-workshop mode controls the choice options in (1) and (2). Mandatory questions by the system aim at teaching when and how to consider audience-design concepts. Accordingly, the users get trained in text production similar to elementary school children, who also tend to omit clues for the reader. Importantly, we illustrate how to make the dialogues of these components intuitive and easy to use to avoid overtaxing the user. In the following, we report evaluation results with different user groups.